Safety of Proton Pump Inhibitors in Pediatric Population: A Systematic Review - Deekshitha Alla; Dhruv Jayeshkumar Shah MBBS; Muneesh Seepana MBBS; Rishabh Baskara Salian MBBS; Sai Santhosha Mrudula Alla MBBS; Midhun Krishna Mohanan MBBS; Mert Sabıroğlu; Mohan Sai Sunith Vegesna MBBS; Aradhya Singh; Srajan Gupta MBBS; Shushrutha Shivalingappa Rekha MBBS (SAGE Publishing, 2024)
Objective. Commonly recommended drugs for adults and children include proton pump inhibitors (PPIs), proven effective for treating peptic diseases like stomach ulcers, GERD, and Helicobacter pylori infections in children over 1-year-old. Yet, prolonged PPI use carries higher risks of adverse reactions, prompting this study's analysis. Methods. We have performed a systematic review of 30 articles, which include a total of 762 505 pediatric patients. Results. Adverse effects were encountered in 6.98% of the population. The 5 most common adverse effects were respiratory tract complications, gastrointestinal complications, urinary tract infections, asthma, and ENT infections. Conclusion. Hence, PPIs should be prescribed only when necessary, and physicians should prioritize patient education when considering their use.